Method of Levels: Is it the Most Parsimonious Psychological Therapy Available? - Mansell, Warren (Revista de Psicoterapia, 2018)
In this article, I will introduce Method of Levels (MOL; Carey, 2006) therapy as one simple solution to many of the issues and complexities of mental health provision around the world. First, I will try to explain that the issues surrounding helping people with mental health problems and experiencing chronic psychological distress can be helped through three comprehensive exercises in the integration of the scientific literature: (1) to integrate psychological processes across mental health disorders; (2) to integrate psychological processes into a single core process; and (3) to integrate theories guiding psychological therapies into a unified theoretical account. Second, I will describe the principles of a theory – perceptual control theory (PCT; Powers, 1973) – that provides a unified account of psychological functioning. These principles are control, conflict and reorganisation. Third, I will explain briefly how to deliver the therapy that follows from these principles – MOL. Fourth, I will summarise evidence for the benefits of MOL and its mechanism of change. Finally, I will set forth a vision for how PCT could guide the future of mental health services.